Personality Features in Obesity - Buratta, Livia; Pazzagli, Chiara; Delvecchio, Elisa; Cenci, Giulia; Germani, Alessandro; Mazzeschi, Claudia (Frontiers in Psychology, 2021)
Obesity is a widespread and broadly consequential health condition associated with numerous medical complications that could increase mortality rates. As personality concerned individual's patterns of feeling, behaviour and thinking, it may help in understanding how people with obesity differ from people with normal-weight status in their typical weight-relevant behaviour. So far, studies about personality and BMI associations have mainly focused on broad personality traits. The main purpose of this study was to explore the personality and health associations among a clinical group composed of 46 out-patients with overweight/obesity (Mean age = 55.83; SD = 12.84) in comparison to a healthy control group which included 46 subjects (Mean age = 54.96; SD = 12.60). Both the clinical and control groups were composed of 14 males and 32 females. Several personality and psychopathological aspects were assessed with the Personality Assessment Inventory (PAI). The results of the Analysis of Variance of Aligned Rank Transformed (ART) showed that patients with overweight/obesity reported higher scores for somatic complaints, depression and borderline features than the control group. Logistic regression highlighted specifically that the subscales of the Borderline Features assessing the Negative Relationship contributed to the increased risk of belonging to the clinical group. For the purpose of this study, the role of gender was considered. Present findings highlight the importance of focusing on assessing personality functioning in the health context and on specific characteristics of interpersonal relationships to promote more tailored treatments.